Attitudes of black African mothers towards the use of traditional healing and Western medicine in treatment of newborn infants - Lekgothoane, Nteseng (My University, 2017)
Many Black African mothers take their newborn infants to a traditional healer not long after birth for them to be given treatment to protect them against bad spirits and to aid in their growth and development. However, there are some Black African mothers who do not believe in traditional medicines but rather in western medicine and practices; while others use a combination of approaches. The aim of the study was to understand the different attitudes that mothers of newborn infants have towards the use of traditional and/or western medicine for the treatment of newborn infants. The study employed a qualitative research paradigm which allowed for the understanding of different beliefs and practices of mothers of newborn infants. An interview schedule was used to facilitate data collection. Eighteen participants were recruited through snowball sampling, and thereafter the participants’ responses were analysed using thematic analysis. The study was guided by the Afrocentric approach. A key finding that emerged from the research was that participants were of the view that monthly visits to western-based healthcare clinics were necessary to track the growth and development of their children, while consultations with traditional healers were limited to approximately three visits in the first few months of life. The mothers who were interviewed also indicated a preference for the use of western medicine as opposed to traditional healing. The main conclusion reached was that the use of traditional healing and western medicine are not necessarily mutually exclusive and that mothers were able to see the value of both approaches, despite a preference for biomedicine. Findings also underscored the importance of an Afrocentric theoretical approach for guiding a research project of this nature. Key words: newborn infants, maternal beliefs, traditional healer, traditional medicine, western medicine